Analysis Of The Regularities Of Changing The Amplitude Values Of The Torque On The Driving And Drived Shaft Of A Chain Drive With An Elastic Element - et. al., Azam Abdumajitovich Mamakhonov, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The article provides a structural diagram and the principle of operation of the recommended chain drive with a compound roller of the chain and a driven sprocket with elastic elements. The results of experimental studies to determine the loading of the chain drive shafts are presented. On the basis of the analysis of the laws of motion of the shafts and the constructed graphical dependencies, the substantiation and the main parameters of the developed design of the chain transmission for the driving mechanisms of technological machines are recommended.